COMPARATIVE ANALYSIS OF GROUNDING RESISTANCE VALUE IN SOIL AND SEPTICTANK - Abdul Syakur; Juningtyastuti Juningtyastuti; Arif Dermawan (Diponegoro University, 2008)
The aim of grounding system to protect of electrical equipment and instrumentation system and peopletogether. The lightning stroke near the strucutre of building can damage of equipment and instrumentationsystem. Therefore, it is very important to protect theese electrical and electronic equipment from lightningstrike uses lightning protection system and grounding system.This paper presents kind of grounding system at type of soil and place. The measurement of groundingresistance in soil and septictank have done. Types of soil for grounding resistance measuring aremarshland, clay and rockland.The measurement results of grounding resistance show that value of grounding resistance depend ondeepness of electrode and kind of soil and septictank. Grounding resistance value in septictank is morelower than soil.